Disturbances of the stomatognathic system and possibilities of its correction in patients with craniofacial morphea - Wróblewska, Agnieszka; Polańska, Adriana; Mojs, Ewa; Żaba, Ryszard; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Morphea en coup de sabre and progressive hemifacial atrophy are extremely rare connective tissue disorders causing facial deformity. In extreme cases, morphological disorders are accompanied by symptoms of a clear impairment of the stomatognathic system. The aetiology of the above-mentioned diseases is still unknown. Properly planned therapy in the field of maxillofacial orthopaedics makes it possible to correct the asymmetric pattern of hard tissue growth and thus enable rehabilitation. The task of augmentation techniques is the volumetric supplementation of tissue defects resulting from atrophic processes. The degree of destruction and the extent of changes determine the method of correction. Mild and moderate defects are treated mainly with biomaterials and autologous adipose tissue. The severe course of hemifacial atrophy and morphea en coup de sabre and the associated significant tissue atrophy necessitate the search for more complex methods of treatment. In this paper, we summarize the disturbances of the stomatognathic system in patients with craniofacial morphea, together with an analysis of current treatment options.